Incidence and Prevalence of Chronic Inflammatory Demyelinating Polyradiculoneuropathy: A Systematic Review and Meta-Analysis - Broers, Merel C.; Bunschoten, Carina; Nieboer, Daan; Lingsma, Hester F.; Jacobs, Bart C. (Neuroepidemiology, 2019)
Background: Prevalence and incidence rates of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) are required to determine the impact of CIDP on society. We aimed to estimate the prevalence and incidence of CIDP worldwide and to determine the effect of diagnostic criteria on prevalence and incidence. Method: A systematic review was conducted for all published incidence and prevalence studies on CIDP until May 18, 2017. Methodological quality was assessed using the Methodological Evaluation of Observational Research checklist. We performed a random effect meta-analysis to estimate pooled prevalence and incidence rates. Results: Of the 907 studies, 11 were included in the systematic review, 5 in the meta-analysis of incidence (818 cases; 220,513,514 person-years) and 9 in the meta-analysis of prevalence (3,160 cases; 160,765,325 population). These studies had a moderate quality. The pooled crude incidence rate was 0.33 per 100,000 person-years (95% CI 0.21–0.53; I 2  = 95.7%) and the pooled prevalence rate was 2.81 per 100,000 (95% CI 1.58–4.39; I 2 = 99.1%). Substantial heterogeneity in incidence and prevalence across studies seems to be partly explained by using different diagnostic criteria. Conclusion: These findings provide a starting point to estimate the social burden of CIDP and demonstrate the need to reach consensus on diagnostic criteria for CIDP.